Fingerprinting TCE Sources in a Sedimentary Bedrock Aquifer using Compound Specific Isotope Analysis - Lima, Paulo L.; Aravena, Ramon; Parker, Beth L.; Cherry, John A. (Águas Subterrâneas, 2009)
Chlorinated volatile organic compounds were detected in an industrial facility in the upper part of the underlying sedimentary fractured bedrock aquifer. Several monitoring wells installed at the site were sampled for VOC’s, inorganic parameters and Compound Specific Isotope Analysis (CSIA). A deep municipal well, located approximately 500 meters southwest from the investigated site, was also included in this study. VOC’s were detected in this well and neither the City nor the Ministry of the Environment of the Province of Ontario (MOE) has been able to determine the origin of these compounds. Groundwater for VOC’s analysis and CSIA were therefore collected in the municipal well in order to evaluate the relationship between the Trichloroethene (TCE) detected in the municipal well and the TCE plume detected in the nearby industrial facility. The δ13C values of TCE obtained in groundwater from the monitoring wells were 12 ‰ more depleted than δ13C values obtained for the deep production well. These data and the VOC’s composition indicate that there is no relationship between the TCE plume at the site and the TCE present in the water of the municipal well, suggesting that other potential regional TCE sources are likely to be present in the area.